Comparing the bond strength of Everstick pegs when using two types Of nanoparticles as irrigation solutions (laboratory study) (Latakia University Journal -Medical Sciences Series, 2023)
Aim: This research aims to compare the bonding strength of everstick post when using both silver nanoparticles and chitosan nanoparticles as irrigation solutions during endodontic treatment, and as a final irrigation solutions befor applying everstick post to extracted human teeth, then compare them with sodium Hypochlorite solution.Materials and methods(30) single-canal lower premolars were gathered, they were chosen of close length and size, after cutting the teeth at the cement - enamel junction. The teeth were divided into three groups as follows: The first group:10 premolars were endodontically treated and irrigated with hypochlorite sodium.The second group:10 premolars were endodontically treated and irrigated with nano silver solution.The third group:10 premolars were endodontically treated and irrigated with nano chitosan solution.Then, the post spaces were prepared and finally irrigated before post placement using: in the first group hypochlorite sodium, in the second group nano silver solution, and in the third group nano chitosan solution, then everstick posts have been applied according manufacturer's recommendations.The bonding strength was tested by mechanical testing device (Testometric) using push-out  test, and the statistical analyzes were conducted using spss program version 25.Results:The results of the research showed that the difference in bonding strength in the first group is less than  the second third group and with a statistically significant degree p